Comparing Numerical Methods for Boussinesq Equation Model Problem - Bulut, Hasan (Wiley, 2009)
This article applies three methods to solve a class of nonlinear differential equations. We obtain the exact solution and numerical solution of the Boussinesq equation for certain initial condition. Comparsion of the results with those of other methods have led us to significant consequences. The numerical Solutions are compared with the known analytical solutions. The numerical results demonstrate that those methods are quite accurate and readily implemented. (C) 2008 Wiley Periodicals, Inc. Number Methods Partial Differential Eq 25: 783-796, 2009
Keywords: Adomian decomposition method; Boussinesq equation; homotopy perturbation method; nonlinear partial differential equations; variational iteration method